2020
DOI: 10.1186/s13765-020-00543-9
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of fraxetin from three different substrates using engineered Escherichia coli

Abstract: Fraxetin, which is a simple coumarin, is a phytochemical present in medicinal plants, such as Fraxinus rhynchophylla, and Cortex Fraxini. In plants, it serves as a controller of iron homeostasis. The health-enhancing activities of fraxetin, such as anticancer, neuroprotective and antibacterial activities, are known. Scopoletin 8-hydroxylase (S8H) is a key enzyme involved in the synthesis of fraxetin from scopoletin. Scopoletin can be synthesized either from esculetin by O-methylation or from ferulic acid by fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this respect, plant-based natural products may provide an alternative solution and one such phytochemical class are the coumarins with recognized therapeutic potentials in multiple neuropsychiatric illnesses through antioxidant, neuroprotective, neuromodulator and antidepressant actions( Skalicka-Woźniak et al, 2016 ; Abu-Aisheh et al, 2019 ; Pruccoli, 2019 ; Daliev et al, 2021 ; Koyiparambath et al, 2021 ; Sharifi-Rad et al, 2021 ; Kılıç, 2022 ). One particular coumarin derivative, fraxetin, is an O -methylated coumarin ( An et al, 2020 ), present in many functional foods as well as several dietary supplements with a documented neuroprotective profile mediated primarily through inhibition of oxidative stress ( Pruccoli, 2019 ; Qin et al, 2019 ; Zhang et al, 2021a ). Although the antioxidant, anti-inflammatory, and neuroprotective activities of fraxetin have been described ( Zhang et al, 2021a ), its effects on stress have not been reported in the literature and remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, plant-based natural products may provide an alternative solution and one such phytochemical class are the coumarins with recognized therapeutic potentials in multiple neuropsychiatric illnesses through antioxidant, neuroprotective, neuromodulator and antidepressant actions( Skalicka-Woźniak et al, 2016 ; Abu-Aisheh et al, 2019 ; Pruccoli, 2019 ; Daliev et al, 2021 ; Koyiparambath et al, 2021 ; Sharifi-Rad et al, 2021 ; Kılıç, 2022 ). One particular coumarin derivative, fraxetin, is an O -methylated coumarin ( An et al, 2020 ), present in many functional foods as well as several dietary supplements with a documented neuroprotective profile mediated primarily through inhibition of oxidative stress ( Pruccoli, 2019 ; Qin et al, 2019 ; Zhang et al, 2021a ). Although the antioxidant, anti-inflammatory, and neuroprotective activities of fraxetin have been described ( Zhang et al, 2021a ), its effects on stress have not been reported in the literature and remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial Strains, Plasmids, and Culture Conditions E. coli strains and recombinants were grown in Luria-Bertani (LB) broth at 37 °C (An et al, 2020;Lone et al, 2020). C. acetobutylicum ATCC 824 and the engineered strain BEKW and mutants were grown in clostridial growth medium (CGM) or 2X YTG agar in an anaerobic chamber (Forma Scientific, Marietta, OH, United States) under 4% hydrogen and 96% nitrogen at 37 °C (Jang et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Esculetin can be converted to scopoletin by an O-methyltransferase, and then scopoletin can be synthesized to fraxetin by scopoletin 8-hydroxylase. Ferulic acid can also be synthesized to scopoletin by E. coli, and then further synthesized to fraxetin [36]. Coumarin was found only in NTJ, not in NTF or NTR, which indicated that coumarin was newly generated through fermentation process.…”
Section: /12mentioning
confidence: 98%